2017
DOI: 10.3389/fncel.2017.00284
|View full text |Cite
|
Sign up to set email alerts
|

Primary Spinal OPC Culture System from Adult Zebrafish to Study Oligodendrocyte Differentiation In Vitro

Abstract: Endogenous oligodendrocyte progenitor cells (OPCs) are a promising target to improve functional recovery after spinal cord injury (SCI) by remyelinating denuded, and therefore vulnerable, axons. Demyelination is the result of a primary insult and secondary injury, leading to conduction blocks and long-term degeneration of the axons, which subsequently can lead to the loss of their neurons. In response to SCI, dormant OPCs can be activated and subsequently start to proliferate and differentiate into mature myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(57 citation statements)
references
References 40 publications
0
56
1
Order By: Relevance
“…Isolation and FACS of OPCs from the adult zebrafish spinal cord was adapted from Kroehne et al (2017). Briefly, transgenic Tg( olig2 :eGFP) adult zebrafish of 6–12 months old were terminally anesthetized in 0.1% w/vol Tricaine (Sigma Aldrich) in E3 medium for zebrafish with 10 −5 % v/v methylene blue.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolation and FACS of OPCs from the adult zebrafish spinal cord was adapted from Kroehne et al (2017). Briefly, transgenic Tg( olig2 :eGFP) adult zebrafish of 6–12 months old were terminally anesthetized in 0.1% w/vol Tricaine (Sigma Aldrich) in E3 medium for zebrafish with 10 −5 % v/v methylene blue.…”
Section: Methodsmentioning
confidence: 99%
“…OPCs are subsequently purified by fluorescence activated cell sorting (FACS) and set in culture immediately after sorting. OPCs remain viable and undifferentiated for up to 10 days in vitro (DIV) (Kroehne et al, 2017). At 3 DIV, whole-cell patch-clamp is used to assess their electrical properties.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3C) supports their generation from RG in the adult zebrafish brain. In addition, flow cytometry of double transgenic fish that combine the RG-specific her4.1:mCherry reporter with the OPC-specific reporter olig2:gfp (Shin et al, 2003;Kroehne et al, 2017;Tsata et al, 2019) [Tg(her4.1:mcherry; olig2:gfp)] revealed that 28.6±3.9% of all olig2:GFP cells were mCherry low /GFP high double positive ( Fig. S4B,C).…”
Section: Lineage Tracing Of Radial Glia-derived Newborn Neurons In Thmentioning
confidence: 99%